The impact of aging on the scale of migration - Anzelika Zaiceva (IZA World of Labor, 2014)
Population aging will continue in the future, in both developed and developing countries. This may lead to lower migration, since the desire to migrate declines later in the life cycle. In addition, indirect labor demand effects may also reduce migration. However, migration of the elderly, return retirement migration, as well as mobility of certain specialist workers such as health and longer-term care providers, may increase. Also, in a family context, the emigration of children may have significant consequences for the elderly left behind, both in terms of poverty risk and health care.
Keywords: J14; J61; 330; migration; population aging; elderly migration